Auditory brain-stem evoked response and efferent action - Yasmeen Yakub Gunja (Journal of All India Institute of Speech and Hearing, 1970)
The assumption that the action of the efferent system innervating the outer hair cells is to increase the loudness of the post adapted test tone is supported by manystudies.